OPTIMUM CONDITIONS FOR N-ACETYL GLUCOSAMINE PRODUCTION FROM TIGER SHRIMP (PENAEUS MONODON) SHELL BY SERRATIA MARCESCENS - Halim, Yuniwaty; Hardoko, Hardoko; Handayani, Ratna; Lucida, Vania (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this research was to determine the optimum condition for Serratia marcescens to produce optimum amount of N-acetyl glucosamine using chitin isolated from tiger shrimp (Penaeus monodon) shells. Methods: This research was conducted using submerged fermentation method. The treatments used were various fermentation temperatures (20, 30, and 37°C), pH (6, 7, and 8), and incubation period (2, 4, 6, and 8 days). Results: Chitinolytic index of Serratia marcescens was 2.203±0.59 after 2 days of incubation. Optimum temperature for N-acetyl glucosamine production using S. marcescens was at 30°C. Optimum pH and incubation period for N-acetyl glucosamine production were at pH 8 and 6 days of incubation period. Conclusion: S. marcescens is able to ferment chitin from shrimp shell to produce N-acetyl glucosamine of 41,166.11±4,480.59 mg/l at optimum fermentation condition.